Application of Shape-Memory Stapes in Osteosynthesis of Mandible Fracture - J. Syrovátka; P. Michna; E. Gregušová; R. Hodan (Czech Dental Chamber, 2005)
In treating fractures in maxilla-facial region verious kinds of materials are used. We have tested treatment of lower jaw fracture by means of staples made of TiNi allow. It is a so-called memory alloy, which contracts upon warming up and creates a relatively stable compressive osteosynthesis. It has been indicated in noncomminuted fracture of lower jaw angle. When a staple is used, an inter-jaw fixation should be applied.It is a cheap method and the intervention does not require special instrumentation. TiNi staples are no more used at our workplace for having been replaced with mini and microsplints; however, they still represent a possible method for the treatment of lower jaw fractures.